واقع المسؤولية الاجتماعية للمؤسسات الاقتصادية الجزائرية حالة مجمع سونطراك أنموذجا - غدير علي عبد القادر (Universty Of El-oued جامعة الوادي, 2022)
الملخص: تهدف هذه الدراسة إلى محاولة الكشف عن واقع تطبيق المسؤولية الاجتماعية بالمؤسسات الاقتصادية الجزائرية، وقد تم التطرق في الجانب النظري للبحث عن ماهية المسؤولية الاجتماعية للمؤسسات الاقتصادية، ومن هذا المنطلق تم طرح التساؤل الرئيسي للدراسة وهو: ما واقع تطبيق المسؤولية الاجتماعية في المؤسسات الاقتصادية الجزائرية سوناطراك أنموذجا؟ وقصد الإجابة المؤقتة على الإشكالية المطروحة حاول الباحث وضع الفروض التالية: هناك التزام من قبل إدارة مؤسسة سوناطراك نحو تبني مفهوم المسؤولية الاجتماعية تجاه العاملين، مجسد ببرامج مطبقة على أرض الواقع. هناك التزام من قبل إدارة مؤسسة سوناطراك نحو تبني مفهوم المسؤولية الاجتماعية تجاه المجتمع، مجسد ببرامج مطبقة على أرض الواقع. هناك التزام من قبل إدارة مؤسسة سوناطراك نحو تبني مفهوم المسؤولية الاجتماعية تجاه البيئة، مجسد ببرامج مطبقة على أرض الواقع. هناك التزام من قبل إدارة مؤسسة سوناطراك نحو تبني مفهوم المسؤولية الاجتماعية تجاه العملاء، مجسد ببرامج مطبقة على أرض الواقع. وقصد التحقق من هذه الفروض ميدانيا، فقد تم مباشرة إجراءات البحث في مؤسسة سوناطراك الواقع مقرها بحيدرة – الجزائر العاصمة، حيث وبعد مباشرة جميع الإجراءات الميدانية المتعلقة بمكان البحث تم التفرغ لعملية بناء الاستمارة النهائية للبحث وتطبيقها في الميدان وكذا جمع البيانات والوثائق اللازمة، ليتم في الأخير مناقشة النتائج المتحصل عليها في ضوء الفرضيات الموضوعة، حيث خلصت نتائج البحث إلى تأكيد الفرضية الأساسية والتي مفادها: توجد ممارسة واقعية لمفهوم المسؤولية الاجتماعية في المؤسسة الاقتصادية الجزائرية سوناطراك Abstract : This study aims to attempt to reveal the reality of applying social responsibility in Algerian economic companies. The theoretical aspect of the research addressed the nature of social responsibility of economic companies. From this standpoint, the main question of the study was raised: What is the reality of applying social responsibility in Algerian economic companies, Sonatrach as a model? In order to provide a temporary answer to the problem raised, the researcher attempted to put forward the following hypotheses: There is a commitment by the management of Sonatrach to adopt the concept of social responsibility towards employees, embodied in programs implemented on the ground. There is a commitment by the management of Sonatrach to adopt the concept of social responsibility towards society, embodied in programs implemented on the ground. There is a commitment by the management of Sonatrach to adopt the concept of social responsibility towards the environment, embodied in programs implemented on the ground. There is a commitment by the management of Sonatrach to adopt the concept of social responsibility towards customers, embodied in programs implemented on the ground. In order to verify these hypotheses in the field, the research procedures were initiated at the Sonatrach companies, headquartered in Hydra, Algiers. After initiating all field procedures related to the research site, the process of constructing the final questionnaire form and applying it in the field, as well as collecting the necessary data and documents, was devoted to finally discussing the results obtained in light of the hypotheses set. The research results concluded with confirming the basic hypothesis, which is: There is a realistic practice of the concept of social responsibility in the Algerian economic company, Sonatrach.
أطروحة دكتوراه التخصص : علم الاجتماع المنضمات والموارد البشرية و الاتصال في العلوم الانسانية والاجتماعية
Keywords: المسؤولية الاجتماعية ، المؤسسات الاقتصصادية ، مجمع سونطراك.; Social responsibility; economic institutions; Sonatrach Group.